Broad-band γ-ray and X-ray spectra of NGC 4151 and their implications for physical processes and geometry - Zdziarski, Andrzej A.; Johnson, W. Neil; Magdziarz, Paweł (Monthly notices of the Royal Astronomical Society, 1996)
We study ł-ray observations of NGC 4151 by the Gamma Ray Observatory (GRO)/OSSE contemporaneous with X-ray observations by ROSAT and Ginga in 1991 June and ASCA in 1993 May. The spectra are well modelled by thermal Comptonization and a dual neutral absorber. We also find, for the first time for NGC 4151, a Compton-reflection spectral component in the Ginga/OSSE data. When reflection is taken into account, the intrinsic X-ray energy spectral index is α ∼ 0.8 and the plasma temperature is ∼ 60 keV for both observations, conditions which imply an optical depth of ∼1. The X-ray spectral index is within the range, α≃0.95±0.15, observed from other Seyfert 1s. Also, the OSSE spectra of those and other observations of NGC 4151 are statistically indistinguishable from the average OSSE spectrum of radio-quiet Seyfert 1s. Thus, NGC 4151 observed in 1991 and 1993 has the intrinsic X-ray/γ-ray spectrum typical for Seyfert 1s, and the main property distinguishing it from other Seyfert 1s is a large absorbing column of ∼ 1023 cm−2. We find no evidence for a strong, broad and redshifted Fe Kα line component in the ASCA spectrum of 1993 May. Also, the Compton-reflection component in the Ginga/OSSE spectrum is a few times too small to account for the strength of the broad/redshifted line reported elsewhere to be found in this and other ASCA spectra of NGC 4151. On the other hand, we confirm previous studies in that archival X-ray data do imply strong intrinsic X-ray variability and hardness of the intrinsic spectrum in low X-ray states. An observed softening of the intrinsic X-ray spectrum with the increasing flux implies that variability in γ-rays is weaker than in X-rays, which agrees with the 100-keV flux changing only within a factor of 2 in archival OSSE and GRANAT/SIGMA observations. The relative hardness of the intrinsic X-ray spectrum rules out the homogeneous hot corona/cold disc model for this source. Instead, the hot plasma has to subtend a small solid angle as seen from the source of UV radiation. If the hot plasma is purely thermal, it consists of electrons rather than e+ pairs. On the other hand, the plasma can be pair-dominated if a small fraction of the power is non-thermal.